Children in Digital Age – Serbian Perspective - Savčić, Sanja (Children in Digital Age, 2025)
Abstract:In the digital age, the protection of children’s rights has emerged as one of the most pressing and complex challenges facing modern societies. While fundamental human and children’s rights are clearly defined through international documents such as the UN Convention on the Rights of the Child, and integrated into national legal systems like the Constitution of the Republic of Serbia, the digital environment introduces entirely new risks and opportunities for children. This calls for a reinterpretation of existing rights in the context of the internet and digital technologies, along with the development of adequate legal and institutional mechanisms for protection. This paper analyzes the general and specific legal framework concerning children’s rights in Serbia, with a special focus on their application in the digital sphere. It reviews key legal instruments – including family law, criminal law, and other specialized regulations – as well as the General Protocol for the Protection of Children, which collectively form the institutional basis for child protection. Special attention is given to rights such as the right to privacy, the right to be forgotten, the right to education and information, and the right to freedom of expression and to be heard – all of which acquire new dimensions in the digital context. Beyond legal analysis, the paper explores the role of parents, educational institutions, and other stakeholders in the child protection system. Although Serbia has developed a relatively comprehensive institutional framework, several challenges remain – such as overlapping competencies, the absence of a specialized law on children’s rights, and low awareness of digital risks among both children and adults. The paper highlights that effective protection requires not only legal regulation but also continuous education, multisectoral cooperation, and proactive engagement by all actors involved in a child’s life. In conclusion, the digital age demands a holistic approach to safeguarding children’s rights, recognizing and addressing the unique risks posed by modern technologies. Despite legislative and institutional efforts, practice still reveals gaps in understanding and implementing children’s rights in digital contexts – a key issue to be addressed moving forward, both in Serbia and globally. Keywords: children’s rights, digital age, Republic of Serbia, child protection, privacy, right to be forgotten, internet safety, legal framework, institutional mechanisms